2018
DOI: 10.1161/hypertensionaha.117.10289
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Hypertrophy and Remodeling and Risk of Cognitive Impairment and Dementia

Abstract: Limited information exists on the longitudinal association between the left ventricular (LV) structure and function and future cognitive impairment and dementia in a large population without clinically recognized cardiovascular disease at baseline. The aim of the present study was to investigate the association between cardiac structure and function and risk of dementia and cognitive impairment in the MESA (Multi-Ethnic Study of Atherosclerosis) cohort. Measures of LV structure and function were determined usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 39 publications
(55 reference statements)
2
32
0
1
Order By: Relevance
“…Although this observation is consistent with some prior work,9, 10 the remaining null cognitive results contrast with literature reporting cognitive associations with LVH8 or increased LV mass index3, 28 in aging cohorts that include dementia cases. Although increased LV mass index is an early marker of pathologic LV remodeling, it may not strongly correspond with subtle cognitive changes in cognitively normal individuals or elders with only mild prodromal symptoms of dementia, such as those participants studied here.…”
Section: Discussionsupporting
confidence: 90%
“…Although this observation is consistent with some prior work,9, 10 the remaining null cognitive results contrast with literature reporting cognitive associations with LVH8 or increased LV mass index3, 28 in aging cohorts that include dementia cases. Although increased LV mass index is an early marker of pathologic LV remodeling, it may not strongly correspond with subtle cognitive changes in cognitively normal individuals or elders with only mild prodromal symptoms of dementia, such as those participants studied here.…”
Section: Discussionsupporting
confidence: 90%
“…Our study finding for an association between LVH and CSVD could explain previous observations regarding the effects of LVH on other endpoints [ 18 , 19 ]. Specifically, in a previous meta-analysis, we found LVH to be strongly associated with cognitive impairment and decline [ 19 ], whereas more recent longitudinal studies have shown LVH to be associated with the risk of incident dementia independently of known vascular risk factors [ 89 , 90 ]. Furthermore, multiple studies have shown that LVH is an independent risk factor for stroke [ 16 - 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is critical to find serum indexes to reflect the changes in the epicardial fat volume of patients. Adiponectin is a protein secreted by adipocyte, which can regulate glucose metabolism, improve insulin resistance and fight atherosclerosis, and is expressed obviously lower in the serum of CAD patients (10). Chemerin belongs to the adipocyte-factor family, which has the function of leukocyte chemotaxis and can promote the development of inflammatory response in injured tissues by recruiting inflammatory cells of chemerin receptors (11).…”
Section: Introductionmentioning
confidence: 99%